The effect of thalidomide on the invasive ability of gastric cancer cells by regulating miR-524-5p/FSTL1: Effect of Thal on gastric cancer cells by regulating miR-524-5p/FSTL1 - Qin, Xiaowei; Zhang, Jinjie; Wang, Mengmeng; Feng, Yafei; Zhao, Yanbo; Zhang, Huipeng; Guo, Wei (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effect of thalidomide (Thal) regulating microRNA (miR)-524-5p/follistatin-like protein 1 (FSTL1) on the invasion ability of gastric cancer cells. For this purpose, real-time fluorescent quantitative PCR (RT-qPCR) was used to detect the level of miR-524-5p in GES1, SUN-16, MGC-803, SGC-7901, MKN-28, and MKN-45 cells. Then the MGC-803 and MKN-45 cells would proceed to the next research. The MGC-803 and MKN-45 cells were cultured in vitro and added Thal to the final concentration of (6.25, 12.5, 25, 50, 100) μg/mL. The blank control group only added 0.1% dimethyl sulfoxide (DMSO) culture medium, and cultured for 48 hours. CCK8 was used to detect cell proliferation, and Transwell was used to detect cell invasion. The experiment was divided into a blank control group, Thal group (25 μg/mL Thal-treated cells), Thal+inhibitor NC group, and Thal+miR-524-5p inhibitor group (transfected with inhibitor NC and miR-524-5p inhibitor respectively on the basis of Thal group), cultivated for 48 h. The level of miR-524-5p in the cells was detected by RT-qPCR; the cell invasion was detected by Transwell; the expression of matrix metalloproteinase (MMP)-2, MMP-9, FSTL1 protein in the cells was detected by Western blot. The targeting relationship between miR-524-5p and FSTL1 was verified by dual luciferase. Results showed that compared with GES1 cells, the level of miR-524-5p in SUN-16, MGC-803, SGC-7901, MKN-28, and MKN-45 cells decreased (P<0.05). In MGC-803 and MKN-45 cells, compared with the blank control group, the cell proliferation rate and the number of invasions in the (50, 100) μg/mL Thal treatment groups, and the number of invasions in (6.25, 12.5, 25) μg/mL Thal treatment groups decreased (P<0.05). Compared with the blank control group, the level of miR-524-5p in the cells of the Thal group, Thal+inhibitor NC group, and Thal+miR-524-5p inhibitor group increased (P<0.05), the number of invasions, the levels of MMP-2, MMP-9 and FSTL1 proteins in cells decreased (P<0.05); compared with the Thal group and the Thal+inhibitor NC group, the level of miR-524-5p in the cells of the Thal+miR-524-5p inhibitor group decreased (P<0.05), the number of invasions, the levels of MMP-2, MMP-9, and FSTL1 proteins in the cells increased (P<0.05). Dual luciferase verification revealed that there was a targeting relationship between miR-524-5p and FSTL1. In conclusion, that can up-regulate the expression of miR-524-5p to reduce the expression of FSTL1 protein, inhibit the invasion of gastric cancer cells, and achieve alleviation of the disease.